An examination of the influence of crosswalk marking removal on pedestrian safety as reflected in road user behaviours. (April 2017) - Gitelman, Victoria; Carmel, Roby; Pesahov, Fany; Hakkert, Shalom
Highlights: Road markings were removed from non-signalised crosswalks on multilane urban roads. Treatment sites were associated with higher speeds related to comparison sites. At treatment sites higher obedience of pedestrians to safe crossing rules was observed. Together with general ignoring pedestrian needs to cross by the vehicles. Crosswalk removal brought about worsening in the possibility of safely crossing the road. Abstract: In some local authorities in Israel, road markings were removed from non-signalised crosswalks situated on multilane divided urban roads. This study examined whether this treatment contributes to pedestrian safety, based on the analysis of differences in road user behaviours and pedestrian crossing conditions at sites without crosswalk markings (treatment sites) versus those with the markings (comparison sites). Field observations were conducted at two treatment and four comparison sites, including video-recordings and free-flow speed measurements. The speed data analysis indicated that treatment sites were associated with higher speeds as compared to other sites, at least in one travel direction, and that speed values were sufficiently high to create a threat of severe injury for the crossing pedestrians. Examinations of other road user behaviours showed that treatment sites are associated with higher obedience of pedestrians to safe crossing rules and low rates of pedestrian-vehicle conflicts during the crossing, but also with long waiting times by pedestrians prior to crossing, low rates of giving-way to pedestrians and more vehicles ignoring pedestrian needs to cross. In general, pedestrian crosswalk removal brought about a worsening in the possibility of crossing the road for pedestrians that in combination with high vehicle speeds cannot be recognised as a safety-improving measure. The study did not support the claim that removing a marked crosswalk leads to safety benefits for pedestrians.